PROLEMATIKA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DI SMP NEGERI 7 SAMBAS TAHUN PELAJARAN 2023/2024 - Sonia, Sonia; M. Sabiqul Huda; Rona, Rona (CV. ADIBA ASIHA AMIRA, 2025)
This research originated from the discovery of a problem about Islamic religious education teachers who very rarely use information technology-based learning media at SMP Negeri 7 Sambas. The purpose of this research is to identify internal factors and external factors that cause the problematics of Islamic religious education teachers in using information technology-based learning media at SMP Negeri 7 Sambas in the 2023-2024 academic year. This research used qualitative method with phenomenological research type. Data collection techniques in this study used interview techniques, observation, and documentation. The data analysis techniques used were data reduction, data presentation and conclusion drawing. The data validity checking technique uses source triangulation and member check. The results of research on the problematics of Islamic religious education teachers in using information technology-based learning media at SMP Negeri 7 Sambas, namely: Internal factors that cause the problems of Islamic religious education teachers in using information technology-based learning media are weak teacher competence, lack of teacher interest and teacher age. External factors that cause the problems of Islamic religious education teachers in using information technology-based learning media are lack of facilities, lack of training and limited funds.